2007
DOI: 10.1590/s1516-35982007000400017
|View full text |Cite
|
Sign up to set email alerts
|

Influência das taxas de ganho de peso pré-desmame das vacas e do tipo de pastagem no período pós-parto sobre a eficiência biológica de vacas e de bezerros de corte

Abstract: Objetivou-se com este estudo avaliar a influência de duas taxas de ganho de peso de bezerras (baixa: 340 ± 32 g/dia ou moderada: 490 ± 29 g/dia) do nascimento aos 7 meses de idade e do tipo de pastagem no período pós-parto, quando vacas, sobre sua eficiência biológica e de seus bezerros até o desmame (aos 217 dias). Quando vacas e após o parto, os animais foram mantidos em pastagem nativa (PN) ou em pastagem cultivada (PC). Durante a lactação, vacas com baixa taxa de ganho de peso pré-desmame apresentaram maio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
5
1
7
Order By: Relevance
“…These values are higher than the 138.4 kg obtained in the present study, but the aforementioned authors weaned calves at 182 days of age. Restle et al (2007), working with lactating cows, also observed that higher nutritional level is the factor that determines better biological results at the time of weaning, and asserted that calf performance is essential for the biological efficiency of beef cattle, which is consistent with the conclusions of Ribeiro et al (2001).…”
Section: Parametersmentioning
confidence: 61%
“…These values are higher than the 138.4 kg obtained in the present study, but the aforementioned authors weaned calves at 182 days of age. Restle et al (2007), working with lactating cows, also observed that higher nutritional level is the factor that determines better biological results at the time of weaning, and asserted that calf performance is essential for the biological efficiency of beef cattle, which is consistent with the conclusions of Ribeiro et al (2001).…”
Section: Parametersmentioning
confidence: 61%
“…Calf weight gain is highly dependent on the dam's milk production in the initial phase (Ribeiro et al, 1991;Quadros & Lobato, 1997 Table 4 -Conception period, age at conception, and pregnancy rates in the first and second breeding seasons of 22-to 24-month-old primiparous cows submitted to early weaning or conventional weaning as calves beef cow milk production, as it depends on several factors, including environment and nutritional level (Moojen et al, 1994;Quadros & Lobato, 1997;Freetly & Cundiff, 1998;Restle et al, 2007), genetic line (Fagundes et al, 2004, Cerdótes et al, 2004Vieira et al, 2005), age or parity (Cerdótes et al, 2004), and sex and calf genetic line (Restle et al, 2004a, b). The average milk production of 4.9 L obtained on weaning date is capable of promoting proper calf development, particularly those born from 22-to 24-monthold primiparous cows.…”
Section: Resultsmentioning
confidence: 99%
“…O melhor nível nutricional em vacas em lactação é fator determinante de melhores resultados de eficiência biológica por ocasião do desmame (RESTLE et al, 2007).…”
Section: Resultsunclassified